Предмет: Математика,
автор: rostis26lav2017
помогите решите уравнение
(-4х-3)*(3х+6,9)=0
(2х-5,2)*(3х+6,9)=0
Ответы
Автор ответа:
2
все решение на листочке)
удачи :)
удачи :)
Приложения:
Автор ответа:
1
(-4х - 3)*(3х + 6,9) = 0
-4х -3 = 0 или 3х + 6,9 = 0
1) -4х - 3 = 0
4х = -3
х = -3 / 4 = -0,75
2) 3х + 6,9 = 0
3х = -6,9
х = -6,9 / 3 = -2,3
Ответ: -0,75; -2,3
(2х - 5,2)*(3х + 6,9) = 0
2х - 5,2 = 0 или 3х + 6,9 = 0
1) 2х - 5,2 =0
2х = 5,2
х = 5,2 / 2 = 2,6
2) 3х + 6,9 = 0
3х = -6,9
х = -2,3
Ответ: 2,6; -2,3
-4х -3 = 0 или 3х + 6,9 = 0
1) -4х - 3 = 0
4х = -3
х = -3 / 4 = -0,75
2) 3х + 6,9 = 0
3х = -6,9
х = -6,9 / 3 = -2,3
Ответ: -0,75; -2,3
(2х - 5,2)*(3х + 6,9) = 0
2х - 5,2 = 0 или 3х + 6,9 = 0
1) 2х - 5,2 =0
2х = 5,2
х = 5,2 / 2 = 2,6
2) 3х + 6,9 = 0
3х = -6,9
х = -2,3
Ответ: 2,6; -2,3
Похожие вопросы
Предмет: Алгебра,
автор: defolderare
Предмет: Физика,
автор: lalitaiopp
Предмет: Другие предметы,
автор: fixsperq
Предмет: Математика,
автор: Аноним
Предмет: Алгебра,
автор: raiterfirs